Screening of Amazonian plants from the Adolpho Ducke forest reserve, Manaus, state of Amazonas, Brazil, for antimicrobial activity - Ana Lúcia Basílio Carneiro; Maria Francisca Simas Teixeira; Viviana Maria Araújo de Oliveira; Ormezinda Celeste Cristo Fernandes; Gláucia Socorro de Barros Cauper; Adrian Martin Pohlit (Memorias do Instituto Oswaldo Cruz, 2008)
Tropical forests are species-rich reserves for the discovery and development of antimicrobial drugs. The aim of this work is to investigate the in vitro antimicrobial potential of Amazon plants found within the National Institute on Amazon Research's Adolpho Ducke forest reserve, located in Manaus, state of Amazonas, Brazil. 75 methanol, chloroform and water extracts representing 12 plant species were tested for antimicrobial activity towards strains of Mycobacterium smegmatis, Escherichia coli, Streptococcus sanguis, Streptococcus oralis, Staphylococcus aureus and Candida albicans using the gel-diffusion method. Active extracts were further evaluated to establish minimum inhibitory concentrations (MIC) and antimicrobial profiles using bioautography on normal-phase thin-layer chromatography plates. Diclinanona calycina presented extracts with good antimicrobial activity and S. oralis and M. smegmatis were the most sensitive bacteria. D. calycina and Lacmellea gracilis presented extracts with the lowest MIC (48.8 µg/ml). D. calycina methanol and chloroform leaf extracts presented the best overall antimicrobial activity. All test organisms were sensitive to D. calycina branch chloroform extract in the bioautography assay. This is the first evaluation of the biological activity of these plant species and significant in vitro antimicrobial activity was detected in extracts and components from two species, D. calycina and L. gracilis.